Interoperability Issues of Earth Observation Grid Systems - Shelestov, A.; Skakun, S.; Korbakov, M. (Інститут програмних систем НАН України, 2008)
In this paper we review issues of Earth observation Grid systems integration. We describe different approaches for the solution of problems of certificate trust, data transfer, geospatial data access, task management, etc. As an example, we describe InterGrid system for environmental and natural disaster monitoring that integrates several regional and national Grid systems.